Elastocaloric cooling - Kabirifar, Parham (Strojniški vestnik, 2019)
The elastocaloric cooling, utilizing latent heat associated with martensitic transformation in shape-memory alloys, is being considered in the recent years as one of the most promising alternatives to vapour compression cooling technology. It can be more efficient and completely harmless to the environment and people. In the first part of this work, the basics of the elastocaloric effect (eCE) and the state-of-the-art in the field of elastocaloric materials and devices are presented. In the second part, we are addressing crucial challenges in designing active elastocaloric regenerators, which are currently showing the largest potential for utilization of eCE in practical devices. Another key component of elastocaloric technology is a driver mechanism that needs to provide loading for active elastocaloric regenerators in an efficient way and recover the released energy during their unloading. Different driver mechanisms are reviewed and the work recovery potential is discussed in the third part of this work.
Keywords: active elastocaloric regenerators; aktivni elastokalorični regeneratorji; cooling; doba utrujanja; driver mechanism; elastocaloric effect; elastokalorični učinek; fatigue life; hlajenje; pogonski mehanizem